A comparison of 3 rheumatoid arthritis disease activity indices in routine clinical practice - Amit Kumar Das; Rathindra Nath Sarkar; Chandan Kumar Das; Ritasman Baisya; Urmimala Bhattacharjee; Pallab Biswas; Akashdip Bhattacharya (Indian Journal of Rheumatology)
Objective: The objective of this study was to appraise the correlation and agreement of RAPID 3 with DAS 28 and CDAI in terms of measuring disease activity/severity and for monitoring response to treatment at 2 and 4 month follow up. Methods: 105 adult literate persons having rheumatoid arthritis according to the 2010 ACR EULAR revised criteria were included. They were evaluated for disease activity by DAS 28, CDAI, and RAPID 3 scores. Response to treatment at 2 month and 4 month follow up was measured by these scores. Achievement of treatment target was defined as conversion from high/moderate disease activity at initial visit to low activity/remission at follow up visit. Result: The mean DAS 28 (0-10), CDAI (0-76) , RAPID 3 (0-30) were 4.73 , 16.72, 10.72 respectively. There was substantial agreement between DAS 28 and RAPID 3 severity categories (kappa = 0.959, P < 0.0001) and also between CDAI and RAPID 3. Conclusion: In a busy clinical setting, our study has shown usefulness of RAPID3 compared to the two most commonly used indices to assess disease activity in RA, both in terms of measuring quantitative disease activity as well as monitoring of treatment response at follow up visits.